2006
DOI: 10.1080/03235400500094399
|View full text |Cite
|
Sign up to set email alerts
|

Field screening of nine plant extracts for the control of post-flowering insect pests of cowpea,Vigna unguiculata(L.) Walp

Abstract: Crude water extracts of leaves from nine plant species were tested for efficacy against three major post flowering insect pests of cowpea in Samaru, Zaria, located in the northern Guinea savanna of Nigeria. These extracts were evaluated based on the number of pests (thrips, legume pod-borers and pod-sucking bugs complex dominated by Clavigralla tomentosicollis Stals) observed after weekly spraying intervals, pod density per plant, pod damage per plant, and grain yield (Kg/ha). All the leaf extracts gave some l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Homemade aqueous extracts of clove basil controlled hemipteran pests (Amoabeng et al 2013;Oparaeke 2006) and lepidopteran pests (Amoabeng et al 2013) in field applications (Tables 1 and 2). Results of storage trials are inconsistent, with 1 out of 3 trials showing no efficacy against coleopteran pests (Law-Ogbomo and Enobakhare 2007;Mlambo et al 2017;Osipitan et al 2014).…”
Section: Clove Basil (Ocimum Gratissimum)mentioning
confidence: 99%
See 1 more Smart Citation
“…Homemade aqueous extracts of clove basil controlled hemipteran pests (Amoabeng et al 2013;Oparaeke 2006) and lepidopteran pests (Amoabeng et al 2013) in field applications (Tables 1 and 2). Results of storage trials are inconsistent, with 1 out of 3 trials showing no efficacy against coleopteran pests (Law-Ogbomo and Enobakhare 2007;Mlambo et al 2017;Osipitan et al 2014).…”
Section: Clove Basil (Ocimum Gratissimum)mentioning
confidence: 99%
“…In field applications, bitter leaf aqueous extracts were used to control coleopteran pests (Mkenda et al 2015a;Tembo et al 2018), hemipteran pests (Degri et al 2012;Mkenda et al 2015a;Oparaeke 2006;Onunkun 2012;Tembo et al 2018), and lepidopteran pests (Degri et al 2012), with a positive outcome in 6 out of 8 instances and with a level of control inferior or similar to the positive controls (Tables 1 and 2). However, the application of ground plant material to the soil was not effective against termites (Ibrahim and Demisse 2013).…”
Section: Bitter Leaf (Vernonia Amygdalina)mentioning
confidence: 99%
“…The Phytochemical screening of the plant extracts revealed the presence of (alkaloids, tannins, flavonoids, saponin, oxalate) ug/g (Onuh et al, 2005, Dialoke et al, 2014 Infrared spectroscopy of the extracts revealed some bioactive compounds like aldehyde, carboxylic acid, isocyanate, alkenes, alcohol, absorbed at different wave lengths (Oparaeke et al, 2006, Dialoke et al, 2014. The experiment showed that different concentrations of extracts of Ocimum gratissimum inhibited the radial growth, changes in colour and appearance of the media from curtney brown to white at different time-intervals, very pronounced in liquid extracts than powder extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Cowpea (Vigna unguiculata L. Walp) is an annual legume, commonly referred to as southern pea, black pea, crowder, labia, niebe, coupe or frijole (Amadioha, 2001, Hall et al, 2003, Onuh et al, 2005. Cowpeas are leguminous seeds that are widely produced in Africa under marginal production system (Oparaeke et al, 2005;Oparaeke, 2006;Phad, 2004). It performs well even when produced in marginal soils due to their ability to fix substantial nitrogen in the soil.…”
Section: Introductionmentioning
confidence: 99%
“…The filtrate obtained formed the extract that was diluted with an appropriate quantity of water to form the spray solution (Oparaeke et al, 2005;Ahmed et al, 2009). Ogunwolu and Idowu (1997) reported that the crude extract is homogenized in methanol: water solvent.…”
Section: Extractsmentioning
confidence: 99%